(Non-)learning to police: A framework for understanding police learning - Staller, Mario S.; Koerner, Swen (Frontiers in Education, 2022)
For professional policing learning is key. Since learning can be viewed as a complex process between the individual and information, learning takes place within and outside the police system as well as during and before employment. The current conceptual analysis delineates different areas of (non-)learning related to policing and argues for the management of learning as a key issue for the police’s professionalization. According to this assumption a Police Learning Management Framework is presented, in which the relevant areas of learning as well as the related challenges for police learning on an individual and organizational level are specified. The proposed model calls for a more focused view on police learning which is prerequisite for professionally coping with the pressing challenges of contemporary policing.